2004
DOI: 10.1113/jphysiol.2004.072645
|View full text |Cite
|
Sign up to set email alerts
|

In vivo responses of mouse superficial dorsal horn neurones to both current injection and peripheral cutaneous stimulation

Abstract: In the superficial dorsal horn (SDH) processing of noxious and innocuous stimuli is critically dependent on the input-output relationship of its component neurones. Such relationships are routinely examined by assessing neuronal responses to somatic current injection or activation of synaptic inputs. A more complete understanding of input-output relationships would be achieved by comparing, in the same neurone, how the two forms of activation contribute to neuronal output. Therefore, we examined how SDH neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…Selected data recorded under in vivo conditions are also included for comparative purposes. Some aspects of these data have been reported previously (see Graham et al 2004b). …”
Section: E T H O D Smentioning
confidence: 63%
See 1 more Smart Citation
“…Selected data recorded under in vivo conditions are also included for comparative purposes. Some aspects of these data have been reported previously (see Graham et al 2004b). …”
Section: E T H O D Smentioning
confidence: 63%
“…S1). 1 When compared with the proportion of SDH neuron discharge profiles encountered in vivo (Graham et al 2004b), both RT and PT proportions showed some similarities. For example, the prevalence of initial bursting neurons at RT is similar to the proportion exhibiting this discharge pattern in vivo.…”
Section: Temperature Affects the Prevalence Of Discharge Categoriesmentioning
confidence: 99%
“…This contrasts with the extensive knowledge of these properties for adult SDH neurons (Graham et al 2004(Graham et al , 2007cLopezGarcia and King 1994;Prescott and De Koninck 2002;Ruscheweyh and Sandkuhler 2002;Ruscheweyh et al 2004; Thomson et al 1989). There has only been one study (in young rats) on the development of intrinsic excitability in SDH neurons (Baccei and Fitzgerald 2005).…”
Section: Introductionmentioning
confidence: 59%
“…We have used this method in previously published work on adult mouse SDH neurons (Graham et al 2004(Graham et al , 2008. Rheobase current was defined as the smallest step current that would elicit at least one AP.…”
Section: Data Capture and Analysismentioning
confidence: 99%
See 1 more Smart Citation